2021
DOI: 10.1002/rth2.12530
|View full text |Cite
|
Sign up to set email alerts
|

In vitro characterization of CT‐001—a short‐acting factor VIIa with enhanced prohemostatic activity

Abstract: Background Traumatic injury and the associated acute bleeding are leading causes of death in people aged 1 to 44 years. Acute bleeding in pathological and surgical settings also represents a significant burden to the society. Yet there are no approved hemostatic drugs currently available. While clinically proven as an effective pro‐coagulant, activated factor VII (FVIIa) use in acute bleeding has been hampered by unwanted thromboembolic events. Enhancing the ability of FVIIa to quickly stop a blee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…23 Therefore, along with the current treatment regimen, it is desirable to have a therapeutic agent that could provide patients with additional prohemostatic activity for treating blood loss while having low thrombogenicity risk by being quickly cleared. CT-001, through two newly engineered amino acids in the γ-carboxyglutamic acid domain to provide enhanced clotting activity and 4 N-glycosylation sites expressing desialylated glycans for rapid removal by hepatocytes, 12 may represent such a needed treatment. In this study, N-glycan profile analyses of CT-001 indicated that all four N-glycosylation sites expressed glycan structures.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…23 Therefore, along with the current treatment regimen, it is desirable to have a therapeutic agent that could provide patients with additional prohemostatic activity for treating blood loss while having low thrombogenicity risk by being quickly cleared. CT-001, through two newly engineered amino acids in the γ-carboxyglutamic acid domain to provide enhanced clotting activity and 4 N-glycosylation sites expressing desialylated glycans for rapid removal by hepatocytes, 12 may represent such a needed treatment. In this study, N-glycan profile analyses of CT-001 indicated that all four N-glycosylation sites expressed glycan structures.…”
Section: Discussionmentioning
confidence: 99%
“…The blood flow in liver was reduced to 30% of control. CT-001 is known to be cleared rapidly by hepatocytes 12 . While this reduced blood flow is expected to be sufficient for maintaining the hepatocyte-mediated rapid clearance of CT-001, the PK of CT-001 under traumatic shock remains to be experimentally defined.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations